2012
DOI: 10.1111/j.1558-5646.2012.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Genetic Variation in Desiccation Tolerance in Embryos of the Terrestrial-Breeding Frog, Pseudophryne Guentheri

Abstract: Environmental change often requires evolutionary responses, and therefore understanding the genetic architecture of susceptible populations is essential for predicting their capacity to respond adaptively. However, quantitative genetic studies are rarely targeted at populations considered vulnerable to such environmental perturbations. Here, we assess the level of heritable variation in the ability of embryos to tolerate desiccation stress in Pseudophryne guentheri, a terrestrial-breeding frog that is currentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(73 citation statements)
references
References 76 publications
3
69
1
Order By: Relevance
“…To explore how nonadditive genetic and maternal environmental effects on larval survival may affect Galeolaria 's persistence in variable thermal environments, we estimated covariation in these effects across all environments in which survival was assayed. Encouragingly, we found that nonadditive genetic effects on survival covaried positively across environments, in contrast to recent suggestions that the exposure of unfavorable nonadditive effects by thermal stress (Eads, Mitchell, & Evans, 2012; Lymbery & Evans, 2013) may lead to fitness trade‐offs across stress levels. Here, however, we found no evidence of such trade‐offs.…”
Section: Discussioncontrasting
confidence: 99%
“…To explore how nonadditive genetic and maternal environmental effects on larval survival may affect Galeolaria 's persistence in variable thermal environments, we estimated covariation in these effects across all environments in which survival was assayed. Encouragingly, we found that nonadditive genetic effects on survival covaried positively across environments, in contrast to recent suggestions that the exposure of unfavorable nonadditive effects by thermal stress (Eads, Mitchell, & Evans, 2012; Lymbery & Evans, 2013) may lead to fitness trade‐offs across stress levels. Here, however, we found no evidence of such trade‐offs.…”
Section: Discussioncontrasting
confidence: 99%
“…Predicting the future distributions of ectotherms in a warmer, but also more variable, environment with more extreme thermal episodes at both ends of the thermal scale can be addressed by studying the ability to adapt through evolutionary, behavioral, or plastic responses (23). A number of recent studies suggest that some species of frogs (17), phytoplankton (24), copepods (27, 28), and insects (22) are evolutionarily constrained when it comes to coping with extreme environments due to, e.g., lack of adaptive genetic variation. Thus current and future species distributions will partly depend on migration, behavioral thermoregulation, and physiological plastic responses; the latter being the focus of this study.…”
mentioning
confidence: 99%
“…Rainfall is an important trigger of breeding, it initiates hatching and provides the ephemeral water sources that allow the completion of metamorphosis (Bradford & Seymour, 1988). In concert, these variables potentially create intense selection, likely influencing embryonic mortality, the time taken to hatch (induced when nest sites flood), the rate of larval development and the survival of metamorphs Donnelly & Crump, 1998;Eads et al, 2012). In concert, these variables potentially create intense selection, likely influencing embryonic mortality, the time taken to hatch (induced when nest sites flood), the rate of larval development and the survival of metamorphs Donnelly & Crump, 1998;Eads et al, 2012).…”
Section: Signatures Of Local Adaptationmentioning
confidence: 99%
“…An overall decrease in rainfall, plus increasing variation in precipitation, such as the incidence and severity of drought events, will likely have a severe negative effect on both aquatic and terrestrial-breeding anurans as breeding success, phenology and migration are tightly associated with the presence of water (Todd & Winne, 2006;Walls, Barichivich, & Brown, 2013). For example, frogs in the Australian Pseudophryne genus lay their eggs in burrows in direct contact with the soil, and rainfall keeps embryos hydrated and ultimately floods the burrows (Eads, Mitchell, & Evans, 2012). For example, frogs in the Australian Pseudophryne genus lay their eggs in burrows in direct contact with the soil, and rainfall keeps embryos hydrated and ultimately floods the burrows (Eads, Mitchell, & Evans, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation